The relationship between liver function and neurophysiological factors in depressed individuals: a cross-sectional study using an integrated “East meets West” medicine approach - Ye, Jiajia; Yu, Yunying; Chung, Raymond C. K.; Lian, Xiaowen; Wang, Xin; Cheung, Wai Ming; Tsang, Hector W. H. (Frontiers in Psychiatry, 2023)
Introduction: Depression is a common mental disorder worldwide. The pathology of depression may involve the dysregulation of neurotransmitters and immunity and produce genetic and environmental effects. Traditional Chinese Medicine (TCM) has been practiced for several thousand years and has a different understanding of depression compared to Western medicine. However, this approach has not been widely accepted by scientific communities as TCM mainly focuses on clinical practice. Methods: In this study, we conducted a cross-sectional study among 100 participants in a rehabilitation hospital to analyze the plausible pathways linking TCM-based liver function and depression, which we hypothesized in a prior theoretical review. Results: A significant relationship between adrenocorticotropic hormone and TCM-based liver function was found (r = 0.211, p = 0.041). Cortisol was significantly associated with norepinephrine (r = 0.243, p = 0.015) and adrenocorticotropic hormone (r = 0.302, p < 0.001). A positive significant relationship was also found between norepinephrine and adrenocorticotropic hormone (r = 0.272, p < 0.001). There was no significant relationship between the ratio from low frequency to high frequency and TCM-based liver function (p = 0.690). Discussion: These results suggest that TCM-based liver function can be interpreted using the hypothalamic-pituitary-adrenal axis. This is a pioneering study to examine the mechanisms of depression in relation to liver function by integrating Eastern and Western medical approaches. The findings of this study are valuable for a deeper understanding of depression and public education.